PENGEMBANGAN MODUL ZAT ADITIF BERBASIS KEARIFAN LOKAL PENGOLAHAN MAKANAN MASYARAKAT DESA KARIMUNTING - Neni Haryani; Masriani Masriani; Lukman Hadi; Hairida Hairida; Rahmat Rasmawan (Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to produce a science learning module on additives based on local wisdom that is feasible to use. This research is a development research using a 4-D model by Thiagaradjan. The data collection technique used is indirect communication with data collection tools, namely evaluation evaluation. The feasibility of the module is seen from three aspects, namely content, language, and graphics. Each aspect is assessed by two experts each. The results showed that the additive module based on local wisdom in the community processing of Karimunting Village was very suitable for use in science lessons with a percentage score on the aspect of content and food presentation 88.5%, language 81.3%, and graphics 92.3%.